Container Terminal Supply Chain Integration How Supply Chain Integrated is Skandia Container terminal? - Kurtuluş, Ercan (My University, 2011)
In the current literature, it is recognized that ports/container terminals are perceived as a member of supply chain which provides transportation and logistics services to the supply chain partners as well as infrastructure for loading/unloading of ships. Thus, their competitiveness is increasingly depending on the performance of the whole supply chain. In this basis, ports/container terminals have to be integrated in to supply chain in order to remain competitive and benefit from supply chain integration in the highly competitive environment. Therefore, evaluation of the supply chain integration of the ports has a great importance. The major focus of this study concentrates on supply chain integration of container terminals by exploring the parameters for measurement of container terminal supply chain integration from the literature, including an empirical study about supply chain integration of Skandia Container Terminal by evaluating in which ways and aspects it is integrated into supply chain or not. Research methods consist of wide review of relevant literature of ports and supply chain integration and collection of empirical data on supply chain integration of Skandia Container terminal. Empirical study is based on interviews with two managers of the terminal and four shipping lines. Findings of this research indicate that the terminal operators perceive their terminal is highly integrated in to the supply chain. On the other hand, shipping lines perceive the terminal relatively less supply chain integrated. The weakest links perceived by shipping lines are “terminal’s relationship with shipping lines” and “provision of value added services”. From the findings, it can be understood that there is a significant perception difference between the terminal operators and shipping lines. It has strategic importance to resolve this perception difference since the shipping lines play an important role in selection of container terminals. Additionally, the terminal operators should evaluate their terminal’s supply chain integration in essence of shipping lines perception along with theirs since it is likely that it would be a significant difference.
Keywords: Transport; Teknisk mekanik; Transport; Applied Mechanics